ANALISIS NILAI ETIKA TOKOH-TOKOH DALAM NOVEL PHOSPHORUS, LELAKI YANG MENCARI TEMPAT TERINDAH KARYA RETNO MAWARNI - Mantra, Adi; Wardarita, Ratu (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2022)
The fact that in a literary work, including novels contains a lot of values, especially ethical values which are reflected through the attitudes, behavior, and actions of these characters, it is this that attracts the writer's interest in conducting an analysis of literary works in the form of novels, namely the novel Phosphorus, The Man Who Finding the Most Beautiful Place by Retno Mawarni. The problem of this research is how are the ethical values of the characters in the novel Phosphorus, The Man Who Sees the Most Beautiful Place by Retno Mawarni. The purpose of this study is to find out and describe the analysis of the ethical values of the characters in the novel Phosphorus, Men Who Seek the Most Beautiful Places by Retno Mawarni. The benefits of research are for teaching Indonesian language and literature, readers of literary works, and other researchers.The research method uses a descriptive method. The data source used is the novel Phosphorus, The Man Who Finds the Most Beautiful Place by Retno Mawarni, which totals 370 pages, published by Sabil, Yogyakarta in July 2012. Data collection techniques used documentation techniques. The approach uses a moral approach, while data analysis techniques use content analysis techniques.Based on the results of the research and discussion, it is known that the novel Phosphorus, The Man Who Finds the Most Beautiful Place by Retno Mawarni is a novel that tells about a young man's efforts to forget his dark past and the efforts he makes to find his identity. As for Faya Nevu or Nevu as the main character, she has good ethical values, namely being liked (al-aliefah), good-natured (anie satun), kindness (al-khairu), and diligent (al-khusyu') as well as bad ethics , namely egoistic and liar nature. Meanwhile, supporting characters, namely Abah Syarif, have good ethics, namely the nature of being liked (al-aliefah) and the nature of kindness (al-khairu). Nitya has good ethics, namely the nature of kindness or al-khairu. Iqbal has good ethics, namely liking (al-aliefah), sweetness (anie satun), and kindness (al-khairu). Gareng has good ethics, namely the nature of being liked or al-aliefah and bad or reprehensible ethics, namely the nature of persecution and the nature of arrogance or arrogance. Doctors Akmal, Bagas, Rieya, and Anton Perdana both have good ethical values, namely being liked or al-aliefah. Rusdi Iskandar has good ethics, namely the nature of goodness (al-khairu). Finally, Satria as a supporting character has good ethical values, namely being liked (al-aliefah). The suggestions that the author can put forward are: (1) for readers and connoisseurs of literature, (2) for teaching Indonesian Language and Literature, and (3) for other researchers.